Incretin-Based Antidiabetic Agents for the Management of Non-Alcoholic Fatty Liver Disease - Nakouti, Theodora; K.A. Karagiannis, Apostolos; Tziomalos, Konstantinos; Cholongitas, Evangelos (Current Vascular Pharmacology, 2015)
Non-alcoholic fatty liver disease (NAFLD) is the commonest chronic liver disease and is more prevalent in patients with type 2 diabetes mellitus (T2DM). Incretin-based antidiabetic agents (glucagonlike peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors) are used in the treatment of T2DM but it is unclear whether they may also play a role in the management of NAFLD. We systematically reviewed the PubMed and Scopus database up to October 2014 and also hand-searched the references of the retrieved articles for studies evaluating the effects of these agents on NAFLD. In animal studies, both GLP-1 receptor agonists and DPP-4 inhibitors reduced transaminase activity and steatosis but their effects on liver inflammation were inconsistent and fibrosis was not assessed. In clinical studies, both agents consistently reduced transaminase activity and steatosis as assessed non-invasively. There are very limited data on the effects of incretin-based treatments on liver histology. In conclusion, GLP-1 receptor agonists and DPP-4 inhibitors appear to hold promise in patients with NAFLD but larger controlled studies with histological and clinical endpoints are needed to evaluate their effects in this population.
Keywords: steatosis